Social Learning Equilibria. Issue 3 (8th May 2020) - Mossel, Elchanan; Mueller‐Frank, Manuel; Sly, Allan; Tamuz, Omer
Abstract : We consider a large class of social learning models in which a group of agents face uncertainty regarding a state of the world, share the same utility function, observe private signals, and interact in a general dynamic setting. We introduce social learning equilibria, a static equilibrium concept that abstracts away from the details of the given extensive form, but nevertheless captures the corresponding asymptotic equilibrium behavior. We establish general conditions for agreement, herding, and information aggregation in equilibrium, highlighting a connection between agreement and information aggregation.